SISTEM INFORMASI E-VOTE PEMILIHAN KETUA HIMPUNAN PRODI SISTEM INFORMASI IBI KOSGORO 1957 BERBASIS WEB - Boy Firmansyah; Dian Gustina (Fakultas Ilmu Komputer dan Desain - Unsurya, 2022)
The process of selecting the chairman of the student rganization at IBI Kosgoro 1957 conducted through voting is still using manual means, and requires coming to the election site and not using a computerized system. This method requires voting time, and waiting for the results of a long vote calculation, because not all students have the same schedule so they cannot attend the election. Oleh therefore made the E-Vote Information System system for the election of the Chairman of the Association of Information Systems Study Programs (Himsisko) at the Kosgoro Institute of Business and Informatics 1957. E-Vote is the solution offered and E-Vote is Web-basedusing PHP and MySQL. This e-vote is for the selection of the chairman of the association to make it easier for each student to choose the chairman of the set in the Information System set (HIMSISKO) through the Web. Website is a formation system site page that can be accessed quickly. This website is based on the development of information and communication technology. PHP Programming Language is used because PHP is the most widely used script programming language today. MySQL is a database management system software. Keywords: E-Vote, Web, PHP, MySQL, Himsisko